2004
DOI: 10.1159/000079883
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Pneumococcal Immunization in Patients with Renal Disease – What Is the Data?

Abstract: Background/Aims: There is an increased incidence of invasive pneumococcal disease in patients with renal allografts, chronic renal insufficiency (CRI), or nephrotic syndrome (NS). Routine pneumococcal immunization (PI) has been recommended for these patients, but the efficacy of PI in this population is not well established. Methods: A review was done of studies that reported the immunologic response, efficacy, or safety of PI in patients with renal allografts, CRI, or NS. Results: On review of 26 published st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 67 publications
(78 reference statements)
0
30
0
Order By: Relevance
“…In the studies with .6-month followup, declining antibody titres were consistently reported, and this decline was usually more rapid than in healthy controls. 70 Very few data are available on responses to 7vPCV in this patient group. A small study has shown that, in children .5 years of age, 7VPCV was immunogenic and that immune suppression did not influence the antibody response.…”
Section: Immunogenicity Of 7vpcv and 23vpcv In At-risk Groupsmentioning
confidence: 98%
“…In the studies with .6-month followup, declining antibody titres were consistently reported, and this decline was usually more rapid than in healthy controls. 70 Very few data are available on responses to 7vPCV in this patient group. A small study has shown that, in children .5 years of age, 7VPCV was immunogenic and that immune suppression did not influence the antibody response.…”
Section: Immunogenicity Of 7vpcv and 23vpcv In At-risk Groupsmentioning
confidence: 98%
“…Vaccine studies in patients with kidney disease have primarily examined antibody response and rate of antibody decline after vaccination as opposed to vaccine efficacy for preventing infection (36). How these alterations in the surrogate outcomes of vaccine responsiveness help to explain observed variation in rates of clinical events as compared with the general population is not well understood.…”
Section: Vaccinationmentioning
confidence: 99%
“…Patients who have kidney disease and are vaccinated with the pneumococcal vaccine seem to develop different serotype-specific titers, develop lower levels of antibody titers, and have a more rapid loss of antibody titers as compared with healthy control subjects (36,44,45).…”
Section: Vaccinationmentioning
confidence: 99%
See 1 more Smart Citation
“…42 Although postvaccination antibody titers in renal transplant recipients are lower than in healthy controls, most patients develop protective titers to at least one pneumococcal serotype. 19,43,44 In one study, the opsonophagocytic assay-a functional measure of vaccine response-revealed that 83% and 80% of patients developed protective titers to any serotype after receiving PPV23 and PCV7, respectively. 45 Although reports in healthy children under 2 years of age suggest that PCV7 is more immunogenic than PPV23, 2 PCV7 has not been shown to have significantly greater efficacy than PPV23 in adult transplant recipients.…”
Section: Pneumococcal Vaccinementioning
confidence: 99%